In-vitro gadolinium retro-microdialysis in agarose gel—a human brain phantom study - Zimphango, Chisomo; Mada, Marius O.; Sawiak, Stephen J.; Giorgi-Coll, Susan; Carpenter, T. Adrian; Hutchinson, Peter J.; Carpenter, Keri L. H.; Stovell, Matthew G. (Frontiers in Radiology, 2024)
Rationale and Objectives: Cerebral microdialysis is a technique that enables monitoring of the neurochemistry of patients with significant acquired brain injury, such as traumatic brain injury (TBI) and subarachnoid haemorrhage (SAH). Cerebral microdialysis can also be used to characterise the neuro-pharmacokinetics of small-molecule study substrates using retrodialysis/retromicrodialysis. However, challenges remain: (i) lack of a simple, stable, and inexpensive brain tissue model for the study of drug neuropharmacology; and (ii) it is unclear how far small study-molecules administered via retrodialysis diffuse within the human brain. Materials and Methods: Here, we studied the radial diffusion distance of small-molecule gadolinium-DTPA from microdialysis catheters in a newly developed, simple, stable, inexpensive brain tissue model as a precursor for in-vivo studies. Brain tissue models consisting of 0.65% weight/volume agarose gel in two kinds of buffers were created. The distribution of a paramagnetic contrast agent gadolinium-DTPA (Gd-DTPA) perfusion from microdialysis catheters using magnetic resonance imaging (MRI) was characterized as a surrogate for other small-molecule study substrates. Results: We found the mean radial diffusion distance of Gd-DTPA to be 18.5 mm after 24 hours (p < 0.0001). Conclusion: Our brain tissue model provides avenues for further tests and research into infusion studies using cerebral microdialysis, and consequently effective focal drug delivery for patients with TBI and other brain disorders.